Preferences Relations and Consumer Theory - Ferreira, M. A. M.; Filipe, J. (arXiv:2111.04741, 2025)
In this paper an interesting application of mathematics in economics is presented: the formulation of the theory of consumer basic problem, grounded on the concept of preferences relation and operationalized with optimization tools.